2019
DOI: 10.1186/s13071-019-3441-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of innate immune responses in sheep PBMCs induced by Haemonchus contortus soluble extracts

Abstract: Background Pattern recognition receptors (PRRs) can recognize pathogen-associated molecular patterns and activate downstream signalling pathways, resulting in modulation of host immunity against pathogens. Here, we investigated whether PRR-mediated recognition is involved in host immune responses to the blood-feeding nematode Haemonchus contortus . Methods During blood-feeding, H. contortus secretes immune-modulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…All these genes are C-type lectin receptor family members, which has been demonstrated for immunomodulatory effects against parasitic infections in the epithelial layer [ 45 ]. Reports have shown that upregulation of C-type lectin genes is beneficial to recognition of parasite antigens, thus activating antigen presentation more effectively [ 31 ], which has a positive effect on disease resistance [ 18 , 49 ]. Based on these reports and our findings, we speculated that the high regulation of lectin receptor genes in the intestinal tissue may enhance the recognition of parasite antigens and present them to the internal immune cells, which can induce the immune system to kill the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…All these genes are C-type lectin receptor family members, which has been demonstrated for immunomodulatory effects against parasitic infections in the epithelial layer [ 45 ]. Reports have shown that upregulation of C-type lectin genes is beneficial to recognition of parasite antigens, thus activating antigen presentation more effectively [ 31 ], which has a positive effect on disease resistance [ 18 , 49 ]. Based on these reports and our findings, we speculated that the high regulation of lectin receptor genes in the intestinal tissue may enhance the recognition of parasite antigens and present them to the internal immune cells, which can induce the immune system to kill the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…These genes were part of the iFMDV-associated co-expression module and many were also part of the DCN. The IFN response was mostly driven by the inactivated vaccine ( Braun et al, 2018 ; Jouneau et al, 2020 ) and the LPS stimulation datasets ( Bush et al, 2020 ), while the helminth infection ( Fu et al, 2016 ; Niedziela et al, 2021 ) and other smaller datasets ( Varela-MartĂ­nez et al, 2018 ; Wang et al, 2019 ; Guo et al, 2020 ) produced a different expression profile, as seen in the stimulation-correlated co-expression modules. In the same manner as known ISGs, lncRNAs can also be induced by IFN and have important roles in controlling pathogen infection and resolution of the immune response, or they can regulate the IFN mediated host defence ( Meng et al, 2017 ; Qiu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NLRC3 has various biological functions. NLRC3 participates in host immunity to pathogens, such as bacteria and parasites (Lewinsohn et al, 2018; Vargas‐Lagos et al, 2019; Wang et al, 2019; Y. Zhang et al, 2019). NLRC3 attenuates autoimmune through downregulating the antigen‐presenting function of dendritic cells via p38 signaling pathway (Fu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%